Wielość: produkcja wspólnotowości - Ratajczak, Mikołaj (Międzywydziałowa „Pracownia Pytań Granicznych” UAM, 2010)
The paper is an attempt to reconstruct the notion of multitude which appears in the work of Antonio Negri, Michael Hardt and Paolo Virno. Multitude refers to the emergence of a new social subject, substantially different from the known historical formulations (nation, people, class). The notion is analyzed both in the context of the classical political philosophy and the changes in the modes of production occuring in the western societies - transition from the material to immaterial labor, which consists of producing relations between social singularities. The genealogical perspective will be therefore supplemented by the analysis of the biopolitical constituion of the multitude and both perspectives will show the exigency to deconstruct numerous notions of the traditional philosophy.
Multitude: production of the common
Keywords: multitude; Foucault; immaterial labor; Virno; Lazzarato; biopolitics; production of subjectivity; Negri; Hardt; immanence of net; globalization; empire; society of control; deconstruction; deterritorialization; composition of labor class